2009
DOI: 10.1021/ef801089c
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bitumen Components in Stabilizing Water-in-Diluted Oil Emulsions

Abstract: Role of bitumen components in stabilization of water-in-diluted oil emulsions was studied using the micropipette technique. Naturally occurring components of bitumen, asphaltenes and maltenes were separated (by precipitating asphaltenes with n-pentane) to investigate their influence on the properties of water drop surfaces in Heptol (a mixture of heptane and toluene at a 4:1 volume ratio). The Heptol-water interfacial tension decreased with increasing adsorption of surface active components from both asphalten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 40 publications
2
62
0
Order By: Relevance
“…The presence (formation) of solid-like (elastic dominant) asphaltene films at the oil-water interface has been shown to significantly hinder the coalescence of two contacting water droplets, as such that when two droplets interact and undergo significant compression, they continue to remain stable without coalescence. 48,51 The correlation between interfacial dilatational elasticity and overall emulsion stability has been qualitatively proven by several researchers, 49,50,[52][53][54][55][56] although there is clear disagreement at high asphaltene concentrations where emulsion stability increases and E' decreases. The discrepancy between the interfacial rheology and emulsion stability is believed to be associated with a change in the interfacial layer structure, transitioning from a compact and rigid monolayer, to a collapsed interfacial layer dominated by threedimensional structures.…”
Section: Asphaltene Adsorptionmentioning
confidence: 95%
See 1 more Smart Citation
“…The presence (formation) of solid-like (elastic dominant) asphaltene films at the oil-water interface has been shown to significantly hinder the coalescence of two contacting water droplets, as such that when two droplets interact and undergo significant compression, they continue to remain stable without coalescence. 48,51 The correlation between interfacial dilatational elasticity and overall emulsion stability has been qualitatively proven by several researchers, 49,50,[52][53][54][55][56] although there is clear disagreement at high asphaltene concentrations where emulsion stability increases and E' decreases. The discrepancy between the interfacial rheology and emulsion stability is believed to be associated with a change in the interfacial layer structure, transitioning from a compact and rigid monolayer, to a collapsed interfacial layer dominated by threedimensional structures.…”
Section: Asphaltene Adsorptionmentioning
confidence: 95%
“…Earlier studies have shown that a water droplet aged in a diluted crude oil or asphaltene solution experienced crumpling upon volume reduction, which was attributed to the irreversible asphaltene adsorption at the oil-water interface. 35,47,48 Following the time-dependent adsorption of asphaltenes, Freer and Radke 49 conducted measurement after replacing the existing solutions with pure solvent for a few times, and reported only a marginal increase in the oil-water interfacial tension (~1.5 mN/m), confirming the irreversible adsorption of most asphaltene molecules. After the washing, the frequency-dependent responses of interfacial dilatational moduli (storage (E') and loss (E") moduli) of the asphaltene film were in excellent agreement with the Maxwell model for irreversibly adsorbed species.…”
Section: Asphaltene Adsorptionmentioning
confidence: 99%
“…Crumpling ratio (CR) 37,38 defined as CR where Af is the projected area of the droplet when crumpling is first observed, and Ai is the initial projected area of droplet, was determined using the Pendant drop apparatus (Section 2.2.3.) to qualitatively evaluate the degree of skin formation.…”
Section: Crumpling Ratiomentioning
confidence: 99%
“…4,5,7,8 Although other bitumen components such as resins and naphthenic acids cannot stabilize water-in-oil emulsions alone, they interact with asphaltenes to enhance emulsion stability. 9,10 Asphaltenes are also known to change the surface properties of hydrophilic solids (clays), making them bi-wettable and enhancing their potential to partition at the oil-water interface. [11][12][13] Solids of intermediate hydrophobicity (water contact angles close to 90 º ) and in the size range of 0.22 -8 m were shown to most effectively stabilize water-in-oil emulsions.…”
Section: Introductionmentioning
confidence: 99%